Role of ICT in developing Smart Agriculture Systems: Digital India Initiatives - Chandak, MB (International Journal of Computer Sciences and Engineering, 2025)
Information and Communication Technology [ICT] with Digital India initiative aims at bringing major revolutionary changes in rural India with focus on developing “Smart Systems”. The Government of India under ministry of Information Technology has launched numerous schemes to promote use of IT in rural area and especially in agriculture sector. Even after regular efforts, the problems are still persisting, due to non availability of regular resources like: power, environmental resources and trained manpower. In agricultural sector farmers suffers due to electricity and irregular weather conditions. This reduces the overall crop production and affects the economy & development of country. The major problems can be classified as: over / under irrigation of crops, non-availability of electric power to operate the water pumps as and when required. The research work presented in the paper is an attempt to design an application to provide solution to farmers and ease the hectic life style. The solution designed is an android based application, with support of “native” language. The presented work is based on Mobile system to fascinate the farmers for operation of day-to-day activities like: motor pump operation, decision making based on weather information, data and message sharing related with crucial activities involved in farming. The system operates irrespective of global location of farmer and equipments.